Some features of ice conditions in the northwestern part of the Arctic Ocean for the period 1979-2022 - Popova V.G.; Rubchenya A.V.; B.V. Ivanov (Российская Арктика)
The article investigates the long-term changes in ice cover and concentration of ice in the northwestern part of the Arctic Ocean (AO) for the period 1979-2022. The data were obtained from the sea ice database created at Arctic and Antarctic Research Institute (AARI). Quantitative comparative assessments of these mentioned ice characteristics are obtained. Taking into account the general ice cover decrease in the study area, three time periods are to be identified. These periods differ in duration, absolute values of sea ice extent and the nature of interannual variability.